Physical properties of tapioca starch-based film indicators with anthocyanin extract from purple sweet potato (Ipomoea batatas L.) and response to pH changes - Rahmadhia, Safinta Nurindra; Sidqi, Afist Azkiya; Saputra, Yanas Anggana (Penerbit Universiti Kebangsaan Malaysia, 2023)
Intelligent packaging comes in the form of interactive film indicator using a natural pigment compound sensitive to pH changes. The development of intelligent packaging as an indicator film by utilizing natural pigment compounds that are related to pH change and food safety is motivated by increased consumer awareness of food safety. Purple sweet potato (Ipomoea batatas L.) is the source of anthocyanin flavonoid compounds sensitive to pH changes, demonstrated by color changes in film indicators. This research aims to determine physical properties and the pH response of tapioca starch-based film indicators with anthocyanin extract variation from purple sweet potato. Purple sweet potato anthocyanin (PSPA) indicator film was made using tapioca starch as biopolymer by casting method with the addition of anthocyanin extract at concentrations of 0, 5, 10, and 15 g. Furthermore, this research is conducted to analyze the physical properties of the film, and response to pH changes of fresh cow milk, Gindara fish fillet and chicken sausage stored at 7 °C and 25 °C under 48-hour observation. The results showed that the film indicator thickness was 0.72-0.74 mm, tensile strength was 1.23-9.86 MPa, elongation was 14.83-55.74%, and water vapor permeability (WVP) was 1.32-1.78 × 10-14 kg.m/m2.s.Pa. The results of this study indicated that the PSPA indicator films have the potential to be used as smart packaging to monitor food freshness and quality for safe consumption. That was supported by the good physical properties of PSPA indicator films.